Axillary Lymph Node Metastasis in Papillary Thyroid Carcinoma at Early Perioperative Period: Report of a Case and Review of the Literature - Cumhur Arıcı; Hasan Çalış; Kenan Demirbakan; Zeki Demirok (Acta Medica Indonesiana)
A 36-year-old woman with a history of neck swelling was diagnosed with papillary thyroid carcinoma, a common but typically slow-growing thyroid cancer with a good prognosis. Despite frequent lymph node metastasis, mortality rates are low. This cancer can rarely spread to unusual areas like the axillary region. The patient had multiple nodules in her thyroid and metastasis to cervical lymph nodes. After a total thyroidectomy and neck dissection, 14 metastatic lymph nodes were found. Post-surgery, radioactive iodine treatment and a whole-body scan revealed axillary lymph node involvement, confirmed as metastasis from the thyroid cancer. Papillary thyroid carcinomas usually have an excellent survival rate, but some can be aggressive. Risk factors for poor outcomes include larger tumors, extracapsular spread, older age, specific variants, and distant metastasis. Surgical removal is the primary treatment, aiming to eliminate local and regional spread. However, metastasis to atypical regions like the axilla is rare and not well understood due to limited data. It’s thought to spread retrograde from the neck or due to abnormal lymphatic flow caused by surgery. Axillary metastasis is often found during or after surgery and may indicate systemic disease. Imaging techniques are used for detection. While it’s usually a sign of poor prognosis, isolated cases without distant metastasis exist. Aggressive thyroid cancer treatment should consider the potential for distant metastases.